Study Quality on Groundwater Consumtion for Households at Economic Development Zone, Saythany District, Vientiane Capital: https://doi.org/10.69692/SUJMRD100170 - INTHASONE, Sengthavi; SILIBOUNTHAN , Somsanouk; CHOMSAIYTHONG, Amphone (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
Water is an important factor for economic-social development, which many countries in the world give importance to the drinking water supply of the people. Drilling underground water to bring water to various activities of households and small business units are many and have a tendency to increase in the future. This study aims to evaluate the quality of underground water by collecting water samples in both seasons at 10 points, 4 of which were analyzed in the field and 12 of which were analyzed in the laboratory. The results of the study found that: in the dry season, the (pH: Potential of Hydrogen Ion) value at points 1, 2, 5-7, 9 and 10 is lower than the standard threshold. (EC: Electrical Conductivity), (TDS: Total Dissolved Solids), Salinity, (TSS: Total Suspended Solids), Turbidity, (NH4-N: Ammonium), (Cl- Chloride), (NO3-N: Nitrate), (As: Arsenic), (Mn: Manganese), (Zn: Zinc), (T-H: Total Hardness as CaCO3), (Fe: Iron) and (F-: Fluoride) all 10 points are within the national environmental standards; (Coliform Bacteria) values ​​at points values ​​at points (2, 4-6 and 8-10) exceed the standard. In the rainy season, the (pH: Potential of Hydrogen Ion) value at point 6 lowers the standard threshold. Salinity, (TSS: Total Suspended Solids), Turbidity, (NH4-N: Ammonium), (NO3-N: Nitrate), (As: Arsenic), (Mn: Manganese), (Zn: Zinc), (Fe: Iron) and (F-: Fluoride) which are within the standard range; In which (Coliform Bacteria) all 10 points and (T-H: Total Hardness as CaCO3), (EC: Electrical Conductivity), (TDS: Total Dissolved Solids), (Cl- Chloride) in the 8th point have high values ​​beyond the national environmental standards.